Testosterone potentiates the hypoxic ventilatory response of adult male rats subjected to neonatal stress. Issue 5 (19th March 2014) - Fournier, Sébastien; Gulemetova, Roumiana; Joseph, Vincent; Kinkead, Richard
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? Does testosterone contribute to the enhancement of the hypoxic ventilatory response observed in stressed rats? What is the main finding and its importance? Castration reduces the hypoxic ventilatory response of stressed rats (but not control rats). Neonatal stress disrupts the gonadotrophic axis and its impact on respiratory control. These results bring new insight into the pathophysiology of sleep‐disordered breathing and the sex‐based difference in its prevalence. Neonatal stress disrupts development of homeostatic systems. During adulthood, male rats subjected to neonatal maternal separation (NMS) are hypertensive and show a larger hypoxic ventilatory response (HVR), with greater respiratory instability during sleep. Neonatal stress also affects sex hormone secretion; hypoxia increases circulating testosterone of NMS (but not control) male rats. Given that these effects of NMS are not observed in females, we tested the hypothesis that testosterone elevation is necessary for the stress‐related increase of the HVR in adult male rats. Pups subjected to NMS were placed in an incubator for 3 h per day from postnatal day 3 to 12. Control pups remained undisturbed. Rats were reared until adulthood, and the HVR was measured by plethysmography (fractional inspired O2 = 0.12, for 20 min). We used gonadectomy to evaluate the effects of reducing testosterone on the HVR. Gonadectomy had no effect on the HVR of control animals but reduced that of NMS animals below control levels. Immunohistochemistry was used to quantify androgen receptors in brainstem areas involved in the HVR. Androgen receptor expression was generally greater in NMS rats than in control rats; the most significant increase was noted in the caudal region of the nucleus tractus solitarii. We conclude that the abnormal regulation of testosterone is important in stress‐related augmentation of the HVR. The greater number of androgen receptors within the brainstem may explain why NMS rats are more sensitive to testosterone withdrawal. Based on the similarities of the cardiorespiratory phenotype of NMS rats and patients suffering from sleep‐disordered breathing, these results provide new insight into its pathophysiology, especially sex‐based differences in its prevalence.